Affiliated firms and financial support: Evidence from Indian business groups - Gopalan, Radhakrishnan; Nanda, Vikram; Seru, Amit (Journal of Financial Economics, 2007)
We investigate the functioning of internal capital markets in Indian Business Groups. We document that intragroup loans are an important means of transferring cash across group firms and are typically used to support financially weaker firms. Evidence suggests that an important reason for providing support may be to avoid default by a group firm and consequent negative spillovers to the rest of the group. Consistent with such spillovers, the first bankruptcy in a group is followed by significant drops in external financing, investments and profits of other firms in the group and an increase in their bankruptcy probability.